Examining Multi-Factor Marketing Dynamics on Consumer Purchase Intention: A TikTok Shop Analysis - Rolando, Benediktus (Journal of Business and Economics Research (JBE), 2025)
This study investigates the impact of five pivotal marketing strategies on consumer purchase intention within TikTok Shop, focusing on the dynamic social commerce landscape in Indonesia. By examining content quality, special holiday promotions, influencer marketing, viral marketing, and livestreaming, the research provides comprehensive insights into integrated marketing approaches in short-form video commerce. Utilizing SPSS version 26, data were collected from 100 Indonesian Generation Z consumers actively engaged with TikTok Shop through a structured questionnaire employing a 5-point Likert scale. Rigorous statistical analyses were conducted, including validity testing (r > 0.195), reliability testing (Cronbach's Alpha > 0.70), and comprehensive classical assumption tests. Multiple regression analysis revealed significant positive influences of all marketing elements on purchase intention. Content quality emerged as the most influential factor (t = 97.854, p < 0.001), followed closely by influencer marketing (t = 95.438, p < 0.001), special holiday promotions (t = 93.672, p < 0.001), viral marketing (t = 91.756, p < 0.001), and livestreaming (t = 89.923, p < 0.001). The F-test results (F = 7.845 > F-table 2.31) definitively confirmed the collective significance of these marketing strategies. The research offers critical theoretical contributions to social commerce literature by addressing the multifaceted nature of marketing strategies in digital platforms. By focusing on Generation Z consumers in Indonesia—a market experiencing rapid digital transformation—the study provides unique insights into the effectiveness of social commerce marketing strategies in emerging digital economies. The findings not only illuminate the intricate relationships between various marketing elements and purchase intention but also establish a robust foundation for future investigations in the rapidly evolving landscape of short-form video commerce